PENGEMBANGAN PERANGKAT PEMBELAJARAN PENGAJUAN MASALAH BERBASIS KEUNGGULAN LOKAL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR PADA MATERI BANGUN DATAR KELAS V SDN PALANG - Wardhana, Suhendra Panca (Universitas Negeri Surabaya, 2020)
ABSTRACTThe purpose of this research is to developing instructional which is qualified in which the validity, practicality, and effectiveness through the instructional material on the problem posing special quality local in order to increase creativity and progres on the shape material of the five grade student of Elementary school Palang. This is done because the developed instructional material on the problem posing bassed special quality local to increase creativity and progres on the shape material of the grade five student of elementery school no yet available. This research is done due to the fact that the teachers are still dominant in learning process (teacher centric) even though creativity and knowledge must be owned by the students in the century 21. The development of this research uses 4-D model of Thiagarajan with plan of experiment research one group pretest-postest design. The subject of this research is develop instructional in the field and implemented of the trial class involving student SDN karangagung, and the data analyzed by descriptive qualitative and quantitative method. The research result is that the develop instructional material of the problem posing bassed quality special which is qualified with both categories (good level), and the ability of the teachers to manage learning are getting both categories (good level) too. The result of the this reserach is that on field trial progres there is change of creativity of the student which is shown the level >75 exceeded for each component of the question in the questionnaire, test creativity and progres to classical learning completeness shown the level >75. The congclution of this research is the developed instructional material on the problem posing bassed special quality local which is qualified the validity, practicality, and effectiveness, so this research can to use to increase creativity and progres shape material of the five grade student of Elementary school SDN Palang. Keywords: Development of Instructional Aterial Problem Posing, Bassed Spesial Quality Local, Shape Material, Creativity, and Progres. ABSTRAK Penelitian ini bertujuan untuk mengembangakan perangkat pembelajaran yang memiliki kreteria valid, praktis, dan efektif melalui pembelajaran pengajuan masalah berbasis keunggulan lokal untuk meningkatkan kreativitas dan hasil belajar bangun datar kelas V SDN Palang. Hal ini dilakukan karena perangkat pembelajaran pengajuan masalah berbasis keunggulan lokal untuk meningkatkan kreativitas dan hasil belajar bangun datar kelas V SDN Palang belum tersedia. Pembelajaran di sekolah lebih menekankan pengetahuan dan berpusat pada guru, padahal kreativitas dan pengetahuan harus dimiliki oleh siswa pada abad 21. Pengembangan perangkat pembelajaran mengikuti rancangan 4-D model dengan rancangan uji coba penelitian one group pretest-postest design. Subyek dalam penelitian ini adalah perangkat pembelajaran yang diuji cobakan pada siswa SDN Karangagung dan di implementasikan pada siswa SDN Palang. Data dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa perangkat valid dengan kategori baik, kemampuan guru dalam mengelolah pembelajaran mendapatkan kategori baik, persentase aktivitas siswa yang dikonversi mendapatkan minimal baik. Respon siswa ? 75% positif pada setiap komponen pertanyaan pada angket. Tes kreativitas dan hasil belajar menunjukkan ketuntasan klasikal ?75. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembelajaran pengajuan masalah berbasis keunggulan lokal dikatakan valid, praktis dan efektif sehingga layak digunakan untuk meningkatkan kreativitas dan hasil belajar bangun datar kelas V SDN Palang . Kata Kunci: Pengajuhan Masalah, Keunggulan Lokal, Bangun Datar, Kreativitas, dan Hasil Belajar.